Geometry dependent microstructures: bug or feature? - Hagen, Jan Frederik; Rasch, Michael; Kohl, Stefanie; Schmidt, Michael (Procedia CIRP, 2018)
Selective laser melting (SLM) promises not only geometric freedom, but is envisioned to allow tailored microstructures as well. While the possibility to be able to build chosen microstructures in certain areas of a part is often seen as a feature, the local change in microstructure due to a changing geometry is just as often seen as a bug. Since the formation of microstructure depends on local temperature gradient and solidification rate, simulations must be able to predict both quantities to reflect experimental results. We use thermomechanical simulations on the part scale and thermofluidic simulations on the powder scale to show the influence of geometry on the temperature gradient and solidification rate. Being able to predict these quantities the user can actively decide between feature and bug and adjust process parameters accordingly.
Created from Fastlane, Scopus look-up
Keywords: Cooling rates; Microstructure; Selective laser melting; Simulation

Microscale modelling for powderbed based laser melting: A testbed for new system technology - Hagen, Jan Frederik; Kohl, Stefanie; Schmidt, Michael (Simulation for Additive Manufacturing 2017, Sinam 2017, 2017)
CRIS-Team Scopus Importer:2022-06-05
Keywords: Beam shaping; Microscale simulation; Selective laser melting

Scaling melt pool geometry over a wide range of laser scanning speeds during laser-based Powder Bed Fusion - Döring, Markus; Boussinot, Guillaume; Hagen, Jan Frederik; Apel, Markus; Kohl, Stefanie; Schmidt, Michael (Procedia CIRP, 2020)
Generating dense parts from laser-based Powder Bed Fusion of metals often requires the adaption of laser scanning speed. Thereby, scanning speed is lost as a degree of freedom for tailoring the microstructure. This paper addresses this issue by using an analytical model from literature to achieve equal melt pool width and depth for a range of factor 12 for laser scanning speeds and by examining the resulting specimen densities for this range of scanning speeds. The melt pool width and the melt pool depth of a dense reference specimen are measured. The measured melt pool width and melt pool depth are defined as the target sizes of the melt pool for all examined scanning speeds, as this is expected to result in dense specimens from a geometrical point of view. The target size shall be achieved by using an analytical model from the literature. This strategy is chosen to estimate the necessary energy input for creating dense specimens while avoiding incomplete fusion and keyholing. Defects mechanisms like splatters and cracks are excluded from this initial examination.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Line energy; Melt pool depth; Melt pool geometry; Normalized enthalpy; PBF; Volume energy density